2008
DOI: 10.1590/s0100-67622008000300018
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performance of mangroves Rhizophora mangle and Laguncularia racemosa under field conditions

Abstract: -In mature mangrove plants Rhizophora mangle L. and Laguncularia racemosa Gaerth. growing under field conditions, photosystem 2 (PS2) photochemical efficiency, determined by the ratio of variable to maximum fluorescence (F v /F m ), increased during the day in response to salinity in the rainy seasons. During the dry season, fluorescence values ( Fo) were higher than those observed in rainy season. In addition, Fo decreased during the day in both season and species, except for R. mangle during the dry season. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
3
11
1
1
Order By: Relevance
“…Wang et al (2018) detected violaxanthin pigments at the wavelength spectrum of 417.6, 440.9, and 470.1 nm while Ruban et al (2001) detection was at 470 nm. These pigments were also reported in mangroves with high salinity (Falqueto et al 2008).…”
Section: Resultssupporting
confidence: 68%
“…Wang et al (2018) detected violaxanthin pigments at the wavelength spectrum of 417.6, 440.9, and 470.1 nm while Ruban et al (2001) detection was at 470 nm. These pigments were also reported in mangroves with high salinity (Falqueto et al 2008).…”
Section: Resultssupporting
confidence: 68%
“…Similarly, slightly saline condition (5 ppt) promotes chlorophyll synthesis in the leaves of X. moluccensis. Some studies showed no significant change in chlorophyll concentration in leaves of different mangroves such as Rhizophora mangle, Laguncularia racimosa (Falqueto et al, 2008), Avicennia officinalis, H. fomes, Excoecaria agallocha (Panda et al, 2006). However, most of the studies found a decreasing trend of chlorophyll with increasing salinity in mangroves leaves such as H. fomes (Mitra & Banerjee, 2010), Bruguiera gymnorrhiza, E. agallocha (Nandy (Datta) et al, 2009, Aegiceras corniculatum (Parida et al, 2004), Bruguieraparviflora (Parida et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…By inducing fluorescence in dark-adapted leaves, Strasser et al (2000) derived several equations for the photochemical apparatus that are translated through the JIP test. Although the technique has been applied to several studies related to water and salt stress, its use in mangal areas is still restricted, but it can provide relevant information on the ecophysiological dynamics of mangrove species under field conditions (Naidoo et al 2002, Gonzalez-Mendoza et al 2007, Falqueto et al 2008Pascoalini 2014, Lopes et al 2019, Tognella et al 2022. Furthermore, gas-exchange measurements of mangroves have been widespread and very useful because they provide information on photosynthesis and water-use efficiency quickly and reliably in field conditions (Medina 1999, Soares et al 2015, Larcher et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the photochemical process through Chl a fluorescence measurements and photosynthesis through gas exchange allow the understanding of sink effects on photosynthesis, from leaf light capture to release of chemical energy. Falqueto et al (2008Falqueto et al ( , 2012 and Pascoalini (2014) conducted studies in the mangrove swamp of the Great Vitória Estuarine System (GVES) and found increased photochemical efficiency with salinity, however lower carbon assimilation for R. mangle (Pascoalini 2014).…”
Section: Introductionmentioning
confidence: 99%